Energy-Efficient Coverage of Rechargeable UAV Networks in Forest Scenarios - Chi Zheng; Ting Su; Jianming Liu; Kuo Chi; Yongqin Yang (IEEE Access)
When conducting scientific research or emergency rescue in the forest, it is essential to establish a seamless communication network to ensure the safety of users. This paper investigates the energy efficiency coverage problem of rechargeable seamless uncrewed aerial vehicle (UAV) networks in forest scenarios. Several charging stations are distributed around the forest to provide charging services for UAVs. We first designed an energy efficiency objective function based on the finite difference time domain method (FDTD) radio wave propagation model, and the energy efficiency coverage problem is formulated as a constrained optimization problem. Secondly, the problem is reduced to two subproblems, the coverage maximization problem and the energy minimization problem. A two-stage joint optimization algorithm is proposed based on a binary logarithmic learning algorithm and a simulated annealing algorithm to solve the problem. The simulation proves that the proposed algorithm outperforms the compared algorithms.